2014
DOI: 10.1093/nar/gku157
|View full text |Cite
|
Sign up to set email alerts
|

A non-canonical plant microRNA target site

Abstract: Plant microRNAs (miRNAs) typically form near-perfect duplexes with their targets and mediate mRNA cleavage. Here, we describe an unconventional miRNA target of miR398 in Arabidopsis, an mRNA encoding the blue copper-binding protein (BCBP). BCBP mRNA carries an miR398 complementary site in its 5′-untranslated region (UTR) with a bulge of six nucleotides opposite to the 5′ region of the miRNA. Despite the disruption of a target site region thought to be especially critical for function, BCBP mRNAs are cleaved by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
89
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(92 citation statements)
references
References 36 publications
(60 reference statements)
3
89
0
Order By: Relevance
“…In the Brassicaceae and Cleomaceae (both in the Rosids supergroup of eudictos), miR396 also targets Basic homologs (Debernardi et al, 2012), while in sunflower (Helianthus annus, in the asterid supergroup of eudicots) it has gained a WRKY transcription factor target (Giacomelli et al, 2012). Gains of lineage-specific targets have also been described for the ancient miR156, miR159, miR167, miR398, miR408, and miR482 families Buxdorf et al, 2010;Chorostecki et al, 2012;Brousse et al, 2014;Xia et al, 2015b). These lineage-specific targets frequently have complementarity patterns that include bulged nucleotides, rendering them undetectable by standard plant miRNA target identification software.…”
Section: Conservation and Identification Of Mirna Targetsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Brassicaceae and Cleomaceae (both in the Rosids supergroup of eudictos), miR396 also targets Basic homologs (Debernardi et al, 2012), while in sunflower (Helianthus annus, in the asterid supergroup of eudicots) it has gained a WRKY transcription factor target (Giacomelli et al, 2012). Gains of lineage-specific targets have also been described for the ancient miR156, miR159, miR167, miR398, miR408, and miR482 families Buxdorf et al, 2010;Chorostecki et al, 2012;Brousse et al, 2014;Xia et al, 2015b). These lineage-specific targets frequently have complementarity patterns that include bulged nucleotides, rendering them undetectable by standard plant miRNA target identification software.…”
Section: Conservation and Identification Of Mirna Targetsmentioning
confidence: 99%
“…Alternative approaches that are more sensitive to these diverse complementarity sites have been described to meet this challenge (Chorostecki et al, 2012;Brousse et al, 2014).…”
Section: Conservation and Identification Of Mirna Targetsmentioning
confidence: 99%
“…Central mismatches interfere with repression . However, miR398 in Arabidopsis binds 5'UTR of the blue copper-binding protein mRNA with a bulge of six nucleotides opposite to the 5' region of the miRNA (Brousse et al, 2014). These and other studies led to consensus base pairing rules for a functional plant miRNA-target interaction: little tolerance for mismatches at positions 2-13, with especially little tolerance of mismatches at positions 9-11, and more tolerance of mismatches at positions 1, and 14-21 (Wang et al, 2015a).…”
Section: Mirnas With Extensive Base Pairingmentioning
confidence: 99%
“…php?GDB = Pe) as the "Section 2" described. Previous study had found that besides the opening reading frame, miRNAs can also target the 5-UTR or 3-UTR domain of some genes (Brousse et al, 2014), thus these types of candidate target genes were included in our study. Then a total of putative 271 target genes were obtained for the identified conserved and novel miRNAs (Supplementary Tables S7 and S8).…”
Section: Target Prediction and Function Analysismentioning
confidence: 99%